SAE Technical Paper Series 2017
DOI: 10.4271/2017-01-1211
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Validation of 12V Lead-Acid Battery for Stop-Start Technology

Abstract: As part of the Midterm Evaluation of the 2017-2025 Light-duty Vehicle Greenhouse Gas Standards, the U.S. Environmental Protection Agency (EPA) developed simulation models for studying the effectiveness of stop-start technology for reducing CO 2 emissions from light-duty vehicles. Stop-start technology is widespread in Europe due to high fuel prices and due to stringent EU CO2 emissions standards beginning in 2012. Stop-start has recently appeared as a standard equipment option on high-volume vehicles like the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…New engine technologies can also help reduce idling in traffic. For example, many new vehicles are now equipped with stop-start technology which turns off the engine whenever idling and restarts comfortably when drivers touch the accelerator pedal [65,66]. Fonseca et al [67] reported that a vehicle with a stop-start system had more than 20% CO2 reduction than a similar vehicle without stop-start technology, partly due to zero idling emissions.…”
Section: Idlingmentioning
confidence: 99%
“…New engine technologies can also help reduce idling in traffic. For example, many new vehicles are now equipped with stop-start technology which turns off the engine whenever idling and restarts comfortably when drivers touch the accelerator pedal [65,66]. Fonseca et al [67] reported that a vehicle with a stop-start system had more than 20% CO2 reduction than a similar vehicle without stop-start technology, partly due to zero idling emissions.…”
Section: Idlingmentioning
confidence: 99%
“…Active battery balancing strategy accompanied by BMS for PV-Battery integrated system are conveyed together in the MATLAB-Arduino interfacing experience. Four series-connected lead-acid batteries are employed in this paper to validate the proposed battery balancing methodology for which the relationship between OCV vs. SOC is as shown in Figure 13 [35].…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, the equation ( 9) was decoded in order to determine the coefficients describing the quantitative influence of individual physical variables on the value of the loaded battery voltage. The decoded linear model of the tested object is a quantitative model, which describes the dependence of the loaded battery terminal voltage U as a variable depending on the nominal (rated) capacity Q, the discharge current I, ambient (electrolyte) temperature T and the (technical) state of charge (SOC) k as independent variablesis presented as the expression (10). It makes it possible to know the "degree of influence" of individual independent variables on the dependent variable.…”
Section: Description Of Acid Battery Operating Parametersmentioning
confidence: 99%
“…charging/discharging voltage and the state of charge (SOC) [2]. Very often lead-acid battery model for Stop-Start Technology is a circuit model with two resistance-capacitance (RC) blocks [10]. The simulated battery operating parameters are voltages, currents, and state of charge.…”
Section: Introductionmentioning
confidence: 99%